PENERAPAN MEDIA APLIKASI CANVA PADA TEKS EKSPLANASI DENGAN MENGGUNAKAN MODEL PROJECT BASED LEARNING PADA SISWA KELAS XI SMA NEGERI 4 CIMAHI - Indra Permana; Octaviani Eka Saputri; Iis Siti Salamah Azzahra (IKIP Siliwangi, 2023)
Teaching materials that are usually used only use Power Point, so there is another application that can be used to make teaching materials that are useful for educators, namely the Canva application. In the Canva application there are many templates and image supporting indicators that we will choose according to the material that will be taught to students. The Canva application can be a solution so that students don't feel bored in learning, of course, in Explanatory Text material, because this material explains natural, social, and cultural phenomena. The Canva application media can be a place for students to be creative and think critically in making examples of Explanatory Text based on the Canva application. This research was conducted face to face with a sample of students in class XI IPA 2 SMA Negeri 4 Cimahi. Learning activities are carried out using the Project Based Learning model. The research results show 1). Design of using the Canva application media on explanatory text material, 2). Student worksheet score results after using the Canva application, 3). The results of the questionnaire showing the effectiveness of using the Canva application media were in the very good category, 95% of students said that teaching materials and work on worksheets with the help of the Canva application media made it very easy, quick to understand, and creative.